The investigation of Social CRM in Transforming Young Customers’ Perceptions and attitudes towards consumption at fast food restaurant in China through comparison with Traditional CRM - Chen, Yebai (2014)
The purpose of this study is to explore the effectiveness of Social Customer Relationship Management (Social CRM) approaches within fast food industry in transforming young customers’ perceptions and attitudes towards consumption at fast food restaurant through the comparison with Traditional Customer Relationship Management in convergence with Electronic Customer Relationship Management (E-CRM). Specifically, this study is analysed from the perspectives of company side and college student side.